PERILAKU MASYARAKAT TERHADAP FENOMENA BANJIR - Oot Hotimah (Jurnal Ilmiah Mimbar Demokrasi, 2011)
This research was conducted at Pengadegan, Pancoran under district, South Jakarta district. The goal is to find out people’s behaviour towards neighborhood that is often affected by flooding. The population is all households on Rt. 05, 06, 07, Rw. 01. The sampling technique is simple random sampling, 40 people were heads of households. The results of this study indicate that, people in the region already has a good behaviour because of behaviour related to the things they must do at home and their environment in case of flooding. There were 93,8% residents have good behaviour, while 6,2% of society do things that are not good because it does not make a purchase or supply of trash in the house.